Новые виды орехотворок рода Aylax (Hymenoptera, Cynipidae) европейской части СССР - Дьякончук, Л.А. (Вестник зоологии, 1983)
Three new Aglax species are described: A. ascanica sp. n. (Serratula xeranthemoides MB. inflorescence), A. phaeopappucii sp. n. (Phacopappus trinervius (Steph) Boiss. inflorescence) and A. ruthenicae sp. n. (gall forming in Centaurea ruthenica Lam. inflorescence). A. serraiulae (Mayr) for the first time is shown for the USSR territory as developing in Sarratula bracteifolia (I1]in) Stank. inflorescence. A kerneri (Wach i) male Is described from Nepefa parouflota MB. inflorescence. Key lo Aylax species known from the USSR.